2020
DOI: 10.15585/mmwr.mm6942e1
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and Age Trends in Persons Who Died from COVID-19 — United States, May–August 2020

Abstract: pandemic resulted in approximately 7,900,000 aggregated reported cases and approximately 216,000 deaths in the United States.* Among COVID-19-associated deaths reported to national case surveillance during February 12-May 18, persons aged ≥65 years and members of racial and ethnic minority groups were disproportionately represented (1). This report describes demographic and geographic trends in COVID-19-associated deaths reported to the National Vital Statistics System † (NVSS) during May 1-August 31, 2020, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
257
4
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(282 citation statements)
references
References 7 publications
14
257
4
7
Order By: Relevance
“…Although more excess deaths have occurred among older age groups, relative to past years, adults aged 25–44 years have experienced the largest average percentage increase in the number of deaths from all causes from late January through October 3, 2020. The age distribution of COVID-19 deaths shifted toward younger age groups from May through August ( 9 ); however, these disproportionate increases might also be related to underlying trends in other causes of death. Future analyses might shed light on the extent to which increases among younger age groups are driven by COVID-19 or by other causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Although more excess deaths have occurred among older age groups, relative to past years, adults aged 25–44 years have experienced the largest average percentage increase in the number of deaths from all causes from late January through October 3, 2020. The age distribution of COVID-19 deaths shifted toward younger age groups from May through August ( 9 ); however, these disproportionate increases might also be related to underlying trends in other causes of death. Future analyses might shed light on the extent to which increases among younger age groups are driven by COVID-19 or by other causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Few strategies provide benefit, several have failed, and others are being evaluated. 3-12 Among the strategies under investigation is the infusion of specific antibodies that are present in the plasma of convalescent patients. 7-12 Plasma infusions have not been commonly associated with adverse events 13 and have been associated with improved outcomes in patients who have had other diseases.…”
mentioning
confidence: 99%
“…The racial disparity seen with COVID-19 rates has been associated with differences in household size, social distancing, community education, and ability to work from home which some communities of color do not have [ 7 , 8 ]. These social issues and healthcare disparities have been apparent in the past but have been further amplified by COVID-19 [ 7 , 9 ]. In addition to social factors, studies have also shown that AA have high frequencies of hypertension, diabetes, chronic kidney disease, and obesity, factors associated with poor outcomes from COVID-19 [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%